Кольоровий PR у системі маркетингу сфери харчових продуктів - Ткачук (Стахурська), Світлана Валеріївна (My University, 2025)
У статті розглядається кольоровий піар як маркетинговий інструмент для брендів в сфері харчової промисловості. Аналізується доцільність та напрями застосування типових кольорів PR: білого, зеленого, рожевого, жовтого, сірого, чорного і коричневого. Білий і зелений піар пропонується вважати обов’язковими для харчових брендів, як і для будь-яких. Однак зелений, екологічний, піар є особливо важливим для харчових продуктів. При цьому зелений піар пропонується формувати як складову загального соціально-відповідального піар. Рожевий піар розглядається як неоднозначний напрям формування зв’язків з громадськістю. З одного боку певний шарм, створення асоціативного зв’язку бренду із важливою для суспільства цінністю, може бути успішно реалізоване в межах рекламної стратегії «резонанс». З іншого боку інколи рожевий піар передбачає роздування переваг і приховування недоліків. Цей бік вважаємо таким, що суперечить соціальній відповідальності бренду і є недопустимим, особливо із харчовими продуктами. Як недопустимі розглядаються чорний і коричневий піар.

The article considers colorful PR as a marketing tool for brands in the food industry. Public relations are considered an important direction in the formation of a brand image. The feasibility and directions of using typical PR colors are analyzed: white, green, pink, yellow, gray, black and brown. White and green PR are proposed to be considered must have for food brands, as well as for any brand. However, green, ecological, PR is especially important for food products. At the same time, green PR is proposed to be formed as a component of general socially responsible PR. The latter involves environmental responsibility, responsibility to customers, employees, partners, the state, society as a whole. Ecological PR, in turn, also includes many directions: environmental friendliness of production, packaging, preservation of natural resources, etc. These directions are constantly expanding. Pink PR is considered an ambiguous direction of forming public relations. On the one hand, a certain charm, the creation of an associative connection of the brand with an important value for society, can be successfully implemented within the framework of the «resonance» advertising strategy. On the other hand, sometimes pink PR involves inflating advantages and hiding disadvantages. We consider this side to be contrary to the social responsibility of the brand and is unacceptable, especially with food products. Black PR and brown PR are considered unacceptable. However, you need to perfectly master the tools of anti-crisis PR in order to apply it if necessary, including in the case of competitors using black PR. Brown PR is even more unacceptable than black. Yellow PR can create a hype effect, however, it will be a short-term success that can destroy the brand image in the long term. Therefore, it is inappropriate to use this type of PR in its pure form, while individual, censored elements can be used within the framework of a viral marketing campaign. Thus, white and green PR are must-haves for food brands, pink PR can only be used in a truthful form within an emotional advertising strategy such as resonance. Yellow PR can be used very carefully and only as separate elements within a viral marketing campaign. Black PR and brown PR are unacceptable.
Keywords: піар; PR; зв’язки з громадськістю; кольоровий піар; маркетинг в сфері харчових продуктів; маркетинг; PR харчових брендів; PR у харчовій промисловості; public relations; color PR; food marketing; marketing; PR of food brands; PR in the food industry; кафедра маркетингу